William Pendry Bidelman (1918–2011) *Material for this article was contributed by several family members, colleagues, and former students, including: Billie Bidelman Little, Joseph Little, James Caplinger, D. Jack MacConnell, Wayne Osborn, George W. Preston, Nancy G. Roman, and Nolan Walborn. Any opinions stated are those of the author. (29th November 2016) - Bond, Howard E.
Abstract: William P. Bidelman—Editor of these Publications from 1956 to 1961—passed away on 2011 May 3, at the age of 92. He was one of the last of the masters of visual stellar spectral classification and the identification of peculiar stars. I review his contributions to these subjects, including the discoveries of barium stars, hydrogen-deficient stars, high-galactic-latitude supergiants, stars with anomalous carbon content, and exotic chemical abundances in peculiar A and B stars. Bidelman was legendary for his encyclopedic knowledge of the stellar literature. He had a profound and inspirational influence on many colleagues and students. Some of the bizarre stellar phenomena he discovered remain unexplained to the present day.